NI-10 AVAILABILITY OF AMIDE PROTON TRANSFER-WEIGHTED MRI METRICS IN GLIOMA - Yamashita, Shinji (Neurooncol Adv, 2019)
OBJECTIVE: Chemical exchange saturation transfer (CEST) is a novel MR imaging contrast technique that relies on the molecular characteristics of the sample. Amide proton transfer (APT) imaging is an emerging CEST-based MR imaging technique that is sensitive to mobile proteins and peptides in the tissue. APT imaging has become increasingly recognized as a promising imaging modality for glioma. Several reports suggest that APT signals are a promising imaging biomarker for glioma grading and prediction of molecular marker status. In this study, we assessed the utility of APT imaging in glioma by evaluating the relationship between APT signals and clinical parameters in glioma. METHODS: We enrolled 23 glioma patients (25 lesions) who underwent preoperative MRI with APT imaging and surgery at our institution between May 2018 and July 2019. The median age of patients was 64 years old (range, 14–84). 2 patients had Grade 2, 1 patient had Grade 3, and 22 patients had Grade 4. APT signals were measured inside the ROI that was manually placed in the solid portion of tumor that best represented the entire tumor signal on raw APT images. RESULTS: We could see that the high APT signals seemed to be related to IDH wild status and high glioma grading (IDH status; p=0.171, Grade; p=0.113). Moreover, the high APT signals were significantly strong related to high Mib-1 LI (p=0.0068, cutoff: 3.295%, sensitivity: 83%, specificity: 71%). CONCLUSIONS: APT imaging might be associated with IDH mutation status and glioma grading. Especially, high APT signal was a great predictor of high MIB-1 LI in glioma.